ردود على أوهام حول حق حرية المرأة في الإسلام - Zawawi (زواوي) (MUWAZAH : jurnal kajian gender, 2013)
In the western, is still evolving paradigm that discredit Islam to curb the freedom of women and demeaning position. Consequently, there is a movement for "gender equality". This movement is growing and becoming a trend in various parts of the world to provide "gender equality" between men and women in every life.